How Indonesian Primary Teacher Motivate and Trains Critical Thinking Skills during Pandemic?: A Phenomenological Study - Nikmah, Ernida Ainun; Zubaidah, Enny; Retnawati, Heri (Jurnal Pendidikan Progresif, 2021)
How Indonesian Primary Teacher Motivate and Trains Critical Thinking Skills during Pandemic?: A Phenomenological Study. Objective: This research aims to describe how teachers motivate and train critical thinking skills during the pandemic. Method: This research was a qualitative study with phenomenological type. The data were collected with a phone-call interview. It was then followed up with a WhatsApp-Group discussion of fifteen primary school teachers at a higher level class in Dawe district, Kudus Municipality, Central Java, Indonesia. The interview data were then reduced and presented in the table. Then, they were searched for the sub-themes. The applied analysis was done with Bogdan & Biklen’s stages, consisting of reducing, finding the themes, and connecting the sub-themes. Finding: The interview result analysis resulted in five themes of motivation aspect and three themes dealing with critical thinking skill training. Conclusion: The obtained findings showed that teachers could improve the learners’ learning motivation during the pandemic. However, they could not train the critical thinking skills due to various limitations.Keywords: critical thinking skill, learning motivation, pandemic. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202104